Knowledge Management Practices in Improving MSMEs Innovation: A Systematic Literature Review period 2016-2025 - Tesa Tiara; Dwi Pratiwi; Lumitha Ayu Ningtias; Armalia Reny Wa (Jurnal Studi Pemerintahan dan Akuntabilitas, 2026)
Purpose: This study aims to systematically review andsynthesize existing literature on Knowledge Management (KM)practices and their role in enhancing innovation capabilitiesamong Micro, Small, and Medium Enterprises (MSMEs). Itidentifies key KM mechanisms, explores their relationships withdifferent forms of innovation, and highlights research gaps forfuture studies.Methodology: A Systematic Literature Review (SLR) wasconducted based on the Preferred Reporting Items for SystematicReviews and Meta-Analyses (PRISMA) guidelines. Relevantpeer-reviewed articles published between 2016 and 2025 wereretrieved from Scopus and Google Scholar. A total of 31 articleswere selected using predefined inclusion and exclusion criteriaand analyzed through qualitative content analysis to identifymajor themes, patterns, and relationships between KM practicesand innovation outcomes.Results: The findings reveal that knowledge sharing, leadershipsupport, human resource management practices, and intellectualcapital are key drivers connecting KM with innovation inMSMEs. These practices contribute to product, process, andgreen innovation, particularly when supported by collaborativecultures and continuous capability development.Conclusion: KM serves as a strategic resource for strengtheningMSME innovation and competitiveness.Limitations: This study is limited by database coverage andpublication periods.Contribution: This review provides an integrated framework forunderstanding KM-driven innovation and offers insights forfuture research and MSME development strategies